2009
DOI: 10.1002/ange.200806148
|View full text |Cite
|
Sign up to set email alerts
|

Schnelle Synthese von Benzofluorenen durch selenvermittelte Carbocyclisierungen

Abstract: Ein Ring ist nicht genug: Eine neuartige doppelte Cyclisierung führt ausgehend von Stilbenen über Dihydronaphthaline zu Benzo[b]fluorenen. Der entscheidende Schritt ist eine durch Selenelektrophile in Gegenwart von Lewis‐Säuren vermittelte intramolekulare Knüpfung von C‐C‐Bindungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The treatment of β-keto ester 4a with phenyl selenenyl chloride and titanium tetrachloride resulted only in the 6- endo cyclization product 5a : the corresponding 5- exo cyclization product was not observed. The selenium moiety was eliminated under the reaction conditions as we have already observed in other examples, and the naphthol derivative 5a was isolated in 61% yield. Careful analysis of the product 5a also revealed that a migration of the phenyl group had taken place as this is now found in the 4-position.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The treatment of β-keto ester 4a with phenyl selenenyl chloride and titanium tetrachloride resulted only in the 6- endo cyclization product 5a : the corresponding 5- exo cyclization product was not observed. The selenium moiety was eliminated under the reaction conditions as we have already observed in other examples, and the naphthol derivative 5a was isolated in 61% yield. Careful analysis of the product 5a also revealed that a migration of the phenyl group had taken place as this is now found in the 4-position.…”
mentioning
confidence: 83%
“…Recently, we have reported the synthesis of dihydronaphthalene and benzofluorene derivatives by selenium-mediated cyclizations of malonate moieties onto alkenes . Herein we use a similar approach for the synthesis of the stilbene starting materials based on Mizoroki−Heck reactions, hydrolysis, and condensation steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selenocyclizations are an important approach in organic chemistry which are frequently used to construct various bioactive heterocyclic compounds. 30,31,125 Several reaction products such as selenolactones obtained from selenocylization reactions have been successfully used as substrates in selenium-catalyzed cyclization reactions. 37 In addition, the selenocyclization reaction has been applied in the total synthesis of natural products.…”
Section: Selenocyclizationsmentioning
confidence: 99%
“…[15][16][17][18] More commonly, synthetic transformations such as selenenylations, selenocyclizations and 2,3-sigmatropic rearrangements have been successfully achieved using these reagents under mild reaction conditions. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The application of these reagents in catalysis makes them more suitable reagents in organic synthesis. [34][35][36][37][38][39] Several books, [1][2][3][4][5][6][7][41][42][43] book chapters [8][9][10][11][44][45][46][47][48] and review articles [49][50][51][52][53]…”
Section: Introductionmentioning
confidence: 99%